Poverty as a determinant associated with the main diseases identified in inhabitants of Lodana, Ecuador - Macías, Valeria D.; Macías, Melany M.; Sánchez, Odalis D.; Veloz, Romina A.; Véliz, Edith M.; Moreno, Andrés (Revista Gregoriana de Ciencias de la Salud, 2025)
This research addressed the close relationship between poverty and the prevalence of diseases in the Lodana parish, Santa Ana, Manabí, Ecuador. Its main objective was to analyze how poverty influences health by identifying the primary diseases in a vulnerable population and exploring contextually adapted interventions to improve access to healthcare. A descriptive cross-sectional study methodology was employed, combining quantitative and qualitative analysis through surveys and semi-structured interviews with a sample of thirty people. The most relevant results revealed that poverty, as a social determinant, significantly impacts health, limiting access to essential services, education, and adequate living conditions. The conclusions emphasize the need to implement public policies that address geographic and socioeconomic disparities to promote equitable and sustainable socioeconomic development in Ecuador's most disadvantaged regions.